Analgesia for open abdominal surgery - Wilson, Frederick; Jones, Chris N. (Digestive Medicine Research, 2019)
Optimal analgesia is a crucial part of enhanced recovery after surgery (ERAS) programs. It not only impacts on immediate patient comfort, but is increasingly being recognised as affecting important patient outcomes such as morbidity and length of stay. Following open abdominal surgery, the most favourable multi-modal analgesic technique, although historically included thoracic epidural analgesia, is now increasingly being debated. We review the evidence, both pre-ERAS and post-ERAS, for analgesic techniques for open abdominal surgery and discuss the potential merits and setbacks of different techniques.